2012
DOI: 10.1590/s1983-40632012000100013
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant potential of Psidium guinnensis Sw. jam during storage

Abstract: The araçá (Brazilian guava) jam is a promising alternative for expanding the consumption of this fruit, besides adding value to it and making the Brazilian Savannah fruits known. Therefore, this research aimed to study the physical and chemical characteristics of the araçá jam, as well as to evaluate the presence and behavior of antioxidant compounds and color, during 12 months of storage. The results obtained for centesimal composition, sugars, fibers, pectin, and consistency showed that the use of araçá was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 21 publications
(17 reference statements)
4
11
1
4
Order By: Relevance
“…The data for + a * oscillated at time zero from 9.53 to 11.36 (Table ), with samples DJ1, DJ2 and DJ4 not differing statistically ( P < 0.05) among themselves, and are close to the value reported by Damiani et al . (2012b) in P. guinnensis jam (9.48). With respect to + b * data, time zero values were greater than 35, ranging from 35.73 to 40.63 (Table ), showing the existence of a more marked yellowish color.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data for + a * oscillated at time zero from 9.53 to 11.36 (Table ), with samples DJ1, DJ2 and DJ4 not differing statistically ( P < 0.05) among themselves, and are close to the value reported by Damiani et al . (2012b) in P. guinnensis jam (9.48). With respect to + b * data, time zero values were greater than 35, ranging from 35.73 to 40.63 (Table ), showing the existence of a more marked yellowish color.…”
Section: Resultsmentioning
confidence: 99%
“…Reduced L * at the end of storage were also reported in Psidium guinnensis (Damiani et al . 2012b), apple guava (Mesquita et al . ), soursop (Pinedo et al .…”
Section: Resultsmentioning
confidence: 99%
“…Houve considerável escurecimento da geleia ao longo da armazenagem, com redução significativa (p<0,01) da luminosidade (L*) em aproximadamente 50% ao final da estocagem, o que pode estar relacionado ao efeito da luz, uma vez que foi utilizada embalagem de vidro transparente, e a síntese de compostos escuros não enzimáticos produzidos através da reação de Maillard, fenômeno que geralmente ocorre durante o armazenamento prolongado de alimentos. Damiani et al (2012b) e Chauhan et al (2013 também reportaram escurecimento ao armazenarem geleias de araçá e coco, respectivamente, com considerável redução da L* ao longo da estocagem. Esse escurecimento afetou a aparência do produto durante a estocagem, todavia não se pode afirmar se isto interfere na preferência dos consumidores, uma vez que não foi realizada análise sensorial ao longo do armazenamento da geleia.…”
Section: Resultsunclassified
“…The change in color values may be due to non-enzymatic browning reactions. Damiani et al (2012) noticed a decrease in color of the jam during a year of storage. In addition, Besbes et al (2009) reported the same in their two months' study.…”
Section: Sensory Evaluationmentioning
confidence: 97%